Attributed relational graph matching using genetic algorithm - Khoo, Koh Giok. (2008)
In this thesis, Genetic Algorithm (GA) based optimization procedures for structural pattern recognition in a model-based recognition system using attributed relational graph (ARG) matching technique are investigated.